(untitled) (Archaeologia Adriatica, 2008)
Several valuable discussions about the inscriptions of Roman Epidaurum exist in the archaeological literature, but since epigraphic material remains a primary source for the reconstruction of the history of a given settlement and should be constantly considered, the author offers a contribution to the study of the epigraphic heritage of Roman Epidaurum. Among the forty-some known inscriptions, two inscriptions particularly stand out in terms of significance and importance, both mentioning P. Cornelius Dolabella (CIL III, 1741 and ILJug 636). The content of these inscriptions, which additionally document the actions of the first governor of the Roman province of Dalmatia (legatus Augusti pro praetore) in Epidaurum, allow us to learn that: 1. In the immediate vicinity of the city was a central site for worship of the imperial cult by the peregrine community from the area of "Upper Illyricum" (civitates Superioris provinciae HIllyrici); 2. The citation of eponymous supreme municipal magistrates (duoviri) is certain proof that at the latest in the period of Dolabella’s governorship Epidaurum possessed municipal status; 3. A military unit was present at that period in Epidaurum (Cohors VI Voluntariorum); 4. And its members, given that the name of the unit was noted in the nominative case, had carried out in the city or on city territory some major building activity (road construction?). The remaining inscriptions contain very valuable data about the administrative organization of the city, list the names of magistrates that in a given moment ran the city government, prominent members of the city council and other prominent individuals who had left a record of their good works in the community. On the funerary inscriptions, which are most numerous, the names are preserved of the deceased and those who raised the monument to them, and on the basis of their names and other data from the inscription in certain cases it is possible to determine the ethnic origin of individuals or families as well as their social status.